DIVERSIFIKASI DAN BRANDING PRODUK OLAHAN BAHAN IKAN PADA UMKM KERUPUK TENGIRI DI PENGKOL JEPARA - Sofwan, Ali; Riyoko, Sisno; Safrizal; Indra Pratama, Fandy; Kusumodestoni, Raden Hadapiningradja; Nor Laila, Azzah (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Fish crackers produced by local MSMEs in Pengkol vary in type, including regular and premium (super) crackers, with mackerel-based crackers serving as the flagship product among 20 MSMEs. This community service program addresses partner challenges primarily in two areas: production and management. On the production side, identified issues include a lack of product innovation, outdated packaging, and the absence of a strong branding image. On the management side, problems include the lack of financial bookkeeping and poor organization of production facilities. This program aimed to enhance partner empowerment in managing product diversification and innovation, as well as in financial and production layout management. The service activities involved socialization, training on new product innovations, branding strategies, market expansion approaches, and financial management. These were followed by mentoring, technology implementation, and evaluation. The outcomes of the program include the adoption of new packaging design, use of cracker drying tools, and implementation of financial management applications. The results show an 80% improvement in partner empowerment related to product innovation and management, and another 80% improvement in financial and production layout management. Product diversification outputs include frozen food innovations such as empek-empek, ekado, and redesigned packaging. Partners are now able to manage their finances using applications and organize drying processes more efficiently using stainless steel clothespins. Regarding participant feedback, 80% strongly agreed and 20% agreed on the usefulness of the program. In terms of material relevance, 85% strongly agreed it met partner needs, and 15% agreed. — Kerupuk ikan yang diproduksi sangat variatif, ada kerupuk dari bahan ikan biasa, dan ada pula kerupuk super dari bahan ikan Tengiri. Kerupuk Tengiri menjadi unggulan produk UMKM di Pengkol dengan jumlah 20. Permasalahan mitra yang menjadi prioritas pada aspek produksi dan manajemen. Aspek produksi yakni belum adanya inovasi produk hasil olahan bahan ikan selain kerupuk, kemasan tampak kuno, dan belum mempunyai branding image produk. Aspek manajemen yakni belum adanya pengelolaan pembukuan keuangan, dan tata kelola tempat usaha. Tujuan program pengabdian ini adalah meningkatkan keberdayaan mitra dalam pengelolaan dan inovasi diversivikasi produk, dan meningkatkan keberdayaan mitra dalam mengelola keuangan dan tata letak produksi. Metode pengabdian melalui lima tahapan, sosialisasi, pelatihan inovasi produk baru, branding, dan strategi membuka peluang pangsa pasar baru, dan pengelolaan keuangan. Kemudian tahap pendampingan, penerapan teknologi, dan evaluasi. Hasil pengabdian ini menunjukkan penerapan teknologi desain kemasan baru, alat jemuran kerupuk, dan aplikasi keuangan. Hasil kegiatan ini menunjukkan peningkatkan keberdayaan mitra dalam pengelolaan dan inovasi produk mencapai 80%; peningkatkan keberdayaan mitra dalam mengelola keuangan dan tata letak produksi 80%. Hasil diversifikasi produk berupa inovasi produk frozen food empek-empek, ekado, dan packaging baru. Mitra mampu mengelola keuangan menggunakan aplikasi dan tata letak untuk penjemuran kerupuk lebih rapi menggunakan jemuran stainless. Peserta 80% merespon sangat setuju, 20% setuju atas kebermanfaatan kegiatan. Pada aspek materi 85% sangat setuju sesuai kebutuhan mitra, dan 15% merespon setuju.